Necessary characteristics for publication in nursing journals: a scoping review (Research, Society and Development, 2022)
Objective: to analyze the scientific evidence available in the literature on the characteristics necessary for the publication of articles in scientific journals in the nursing field. Methodology: scoping review, with the aim of answering following the question: What is the scientific evidence available in the literature about the necessary characteristics for the publication of articles in nursing journals? Studies available in full were included, which addressed scientific writing, related to the relevant characteristics for publication, without delimitation of language and time of publication. Nine search sources were used. Results: 6,286 articles were found. Of these, 68 were eligible, and 12 articles were included. Most studies addressed items such as title, abstract, introduction, method, results, conclusion, references and questions regarding the characteristics of the writing and language used. Conclusion: The quality of the article is directly related to the characteristics present in it, whether in relation to the writing itself, as well as good practices for carrying out the research.